Synthesis, electrochemistry and in situ spectroelectrochemistry of novel hexadeca-substituted phthalocyanines with three different groups - KOCA, ATIF (ELSEVIER SCIENCE SA, 2015)
The synthesis, characterization and voltammetric and spectroelectrochemical properties of newly synthesized metallophthalocyanines (M=Co, Cu, Cl-In, Cl-Mn) containing eight hexyloxy groups on non-peripheral positions together with four chloro and four 2-naphthoxy groups on peripheral positions have been presented in this work. Satisfactory yields of the phthalocyanines have been achieved by using microwave heating. The phthalocyanine derivatives have been characterized by using fourier transform infrared spectroscopy, proton and carbon nuclear magnetic resonance, mass and UV-vis spectroscopy techniques. Electrochemical studies on hexadeca-substituted phthalocyanines have been reported in this paper. In addition to typical voltammetric responses of the common octa and tetra substituted MPc's, copper (3) and indium (4) derivatives showed completely different in situ spectroelectrochemical responses with very sharp and intense absorption bands for the anionic forms of these complexes. The aggregation behaviours of the phthalocyanine complexes were also investigated in different solvents and concentrations. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Metallophthalocyanines; Hexadeca-substituted; Hexyloxy groups; 2-Naphthoxy groups; Electrochemistry; Spectroelectrochemistry; MICROWAVE-ASSISTED SYNTHESIS; METAL-FREE; MANGANESE PHTHALOCYANINE; PHOTOPHYSICAL PROPERTIES; COBALT; COPPER; COMPLEXES; OXIDATION; CO(II)